True Singapore Ghost Stories : Book 1 - Russell Lee
Book 1 of Singapore's all-time best-selling series - over 500,000 copies sold. True stories to make your toes curl, your hair stand. Singaporeans speak out on the most frightening experiences of their lives! More than 70 true stories as related by executives, professionals, workers, and students! Every one an eyewitness account.